The Political U: New Evidence on Democracy and Income - Nauro F. Campos; Fabrizio Coricelli; Marco Frigerio (Institute of Labor Economics (IZA), 2022)
This paper throws new light on the relationship between income and democracy. Using data for 162 countries over 1960-2018, we show that the causal relationship between political and economic development is U- shaped: "intermediate" political regimes significantly lead to inferior economic performance vis-à-vis both "democracies" and "autocracies." Our results suggest "intermediate" regimes decrease long run GDP per capita by about 20 percent. These effects are mainly driven by political instability, while other potential mechanisms, such as education, investment and inequality, lack comparable empirical support. These findings are robust to, among others, using night-lights instead of GDP, different democracy measures and estimators.
Keywords: C33; D72; F15; O43; P16; 330; democracy; income; growth; political development; economic development; non-linearity